Pilot study of a mindfulness‐based, multi‐component, in‐school group sleep intervention in adolescent girls. Issue 2 (3rd July 2012) - Bei, Bei; Byrne, Michelle L.; Ivens, Clare; Waloszek, Joanna; Woods, Michael J.; Dudgeon, Paul; Murray, Greg; Nicholas, Christian L.; Trinder, John; Allen, Nicholas B.
Abstract Aim Existing literature links poor sleep and anxiety symptoms in adolescents. This pilot study aimed to develop a practical method through which a program to improve sleep could reach adolescents in need and to examine the feasibility of a mindfulness‐based, multi‐component group sleep intervention using sleep and anxiety as outcome measures. Methods Sixty‐two grade 9 students (aged 13–15) at a girls' school were screened with the Pittsburgh Sleep Quality Index (PSQI) and Spence Children's Anxiety Scale (SCAS). Ten participants with self‐reported poor sleep were enrolled into a six‐session program based on Bootzin & Stevens, with added stress/anxiety‐specific components. Sessions covered key aspects of basic mindfulness concepts and practice, sleep hygiene, sleep scheduling, evening/daytime habits, stimulus control, skills for bedtime worries and healthy attitudes to sleep. Treatment changes were measured by pre‐post scores on the PSQI, SCAS and 7‐day actigraphy‐measured sleep. Results The program demonstrated high acceptability, with a completion rate of 90%. Based on effect‐size analysis, participants showed significant improvement on objective sleep onset latency (SOL), sleep efficiency and total sleep time; actigraphy data also showed significantly earlier bedtime, rise time and smaller day‐to‐day bedtime variation. Post‐intervention global PSQI scores were significantly lower than that of pre‐intervention, with significant improvement in subjective SOL, sleep quality and sleep‐related daytime dysfunction. There were small improvements on some subscales of the SCAS, but change on its total score was minimal. Conclusions A mindfulness‐based, multi‐component, in‐school group sleep intervention following brief screening is feasible, and has the potential to improve sleep. Its impact on anxiety needs further investigation.